Revisit' the silk road: Railway speed-up project export - Hangtian Xu (European Regional Science Association (ERSA), 2014)
China's main railway line linking east and west was speeded-up in Oct. 21, 2000, which improves freight efficiency between eastern China and Xinjiang (the hub of China and Central Asia). This paper tests the impact of exogenous domestic accessibility variation on export. By employing a transaction-level customs database, empirical results find benefited exporters (use rail freight) increase the export value to Central Asia by around 30% compared with exporters use other freight modes, and exporters use rail freight but enjoy limited speeded-up mileage. The speed-up effect is due to mixed channels: net export creation, export diversion in freight modes and exporters. Increase in export value of related exporters is exerted by export expansion of existing exporters but not entry of new exporters. This paper also finds exports of medium value products benefit most from speed-up, which are more sensitive to shipping efficiency than low and high value products. Overall, speed-up effect on regional development of Xinjiang is two-fold. It weakens the function of Xinjiang as the hub, but promotes its export in other international markets by better accessibility to coast.
Keywords: 330; Domestic transport costs; China-Central Asia; Export; Firm-level; Transport infrastructure